Analisis Hukum Ekonomi Syariah Mengenai Online Marketplace Shopee (Studi perbandingan Akad Qardh, Fatwa DSN No 19/DSNMUI/IV/2001 dan ketentuan perjanjian Fitur "SPinjam") - Hajriani, Sesilia; Mursal, Mursal -; Fauzi, Muhammad (Al-Amwal : Journal of Islamic Economic Law, 2023)
This study aims to determine how the Qardh Akad Analysis in the SPinjam Feature on the Shopee Application. Shopee Pinjam (SPinjam) is an online cash loan product that offers loans with a fast, safe, minimal risk and unsecured process. So that SPinjam becomes an alternative for people who need funds. because Indonesia is a majority Muslim community, this Marketplace must be adjusted to Sharia provisions. There is no Fatwa specifically related to the Marketplace. The formulation of the problem in this study How is the mechanism of Terms and Conditions of Shopee Pinjam Services for Loan Recipients on the Shopee Application, How is the Analysis of the Conformity of Qardh Akad with the Terms and Conditions of Shopee Pinjam Services for Loan Recipients on the Shopee Application and How is the Analysis of DSN-MUI Fatwa No: 19/DSNMUI/IV/2001 with the Terms and Conditions of Shopee Pinjam Services for Loan Recipients on the Shopee Application.This type of research is library research, the data analysis method uses normative descriptive methods, uses a fatwa approach and inductive thinking. The results of this study indicate that: Users of the SPinjam feature in the Shopee application are Shopee application users who have reached the gold member level with a certain credit limit. The loan consists of a disbursement fee of 1% monthly installment fee (5%/month) and a monthly SPinjam protection fee (0.25%/month). The conformity between DSN MUI Fatwa No.19/DSN-MUI/IV/2001 and the SPinjam Terms and Conditions of Service document can be concluded that it is not fully in accordance with the provisions of sharia principles. The conflicting points of the SPinjam Document are related to the following; loan repayment system in the form of credit, late fees, loan interest, risk of credit failure for borrowers and dispute resolution institutions